Professores de língua inglesa de escolas públicas brasileiras em um programa de formação continuada nos EUA: um estudo de caso - Cruvinel, Roberta Carvalho (2016)
This study focuses on the continued education of English teachers from Brazilian public schools and aims at investigating the implications of the participation of ten teachers in a Professional Development Program for English Teachers, promoted and funded by Capes in partnership with Fulbright and the Embassy of the United States in Brazil, carried out in the United States, identifing and analyzing the reasons that led these teachers to invest and compete for one of the places offered for the program and also eliciting how the selected teachers experienced it, studying in that country. Narratives of their academic and professional lives, questionnaires and individual interviews constituted the data used in this research. A qualitative approach was adopted in order to collect and analyze data, according to Fetterman (1998). This case study was conducted with the participation of ten teachers, enrolled in three different editions of the program: January, 2012; June, 2012; and June, 2013. The data was analyzed in the light of studies on continued teacher training in a temporal/historical perspective (ALMEIDA FILHO, 1997; CELANI, 2010) and its theoretical developments of continued teacher training for a global society (KUMARAVADIVELU, 2012), as well as on social identity and the notion of investment (NORTON, 2000). The results point out the fact that the English teachers invested to participate in this Program mainly for personal accomplishment reasons through cultural experience, language/communication practice and methodological update. Results also show that continued training courses offered by the universities in the United States for PDPI have occurred in the form of methodological training, thus reinforcing the ideology that training on teaching techniques can be a solution for their teaching problems. Therefore, critical education was not adopted as an educational approach in any of courses from the universities surveyed. As a result, a number of factors continue to nourish the ideology that holds native speakers as reference and orientation towards language learning, which maintains the status quo of the English language upon the basis of ideological imperialism. Nevertheless, all participants evaluated the program positively, once their needs and expectations were met. Moreover, regarding the implications of their participation in the program, the experience has motivated them to improve their lessons regarding the use of English in class, as they returned more confident of their linguistic/communicative potential in the language. They have also gained from the use of various teaching tools and technologies to which they had been exposed to during the program. In addition, the experience has motivated them to seek more training in post-graduate programs.